Climate change and its impact on soil and food security (Development Engineering Conferences Center Articles Database, 2025)
Climate change in the 21st century is considered one of the major and important challenges affecting food security and various aspects of human life. Today, ensuring and maintaining food security, given the significant demand of the population and the intense exploitation of limited and non-renewable resources and reserves, is of particular importance and has been a major concern of governments in recent years. The discussion of climate change and its effects on the environment is one of the important topics in studies and research around the world. Limitations Food resources and production resources Due to the rapid population growth, the future of food supply for people is uncertain. Therefore, nutrition plays an important and fundamental role in a healthy lifestyle, cardiovascular diseases, cancer, and the survival of the generation. Ensuring food security, sustainable agriculture, and preserving water and soil resources, along with ecological and social issues and characteristics, and its important strategies and policies, is a controversial approach, given the importance of the issue. The occurrence of droughts, increasing temperatures, greenhouse gas production, and increased factory activity are clear reasons for climate change and the deterioration of food security. Food security and climate change are two inseparable components that directly affect each other. The agricultural sector is considered an important institution in the field of food production, which today faces the challenge of reduced rainfall, soil fertility, climate change, and lack of production potential. Unfortunately, in the past two decades, the phenomena of changing agricultural land use, construction of parks, industrial estates, and infrastructure development have been occurring at an ever-increasing pace, accelerating, and expanding, and are considered a significant threat to food security and threatening the country's economy in the agricultural sector. The purpose of this research is to collect the results of research and materials conducted on this subject and to examine and analyze the effects of climate change on components involved in food security, such as water resources, agriculture, forestry and land use, health, industry, food security, and sustainable national security; and effective methods and solutions have been discussed in this regard.